RATING OF THE REGION’S INVESTMENT POTENTIAL IN RUSSIAN FEDERATION: MULTIDIMENSIONAL STATISTICAL ANALYSIS - Victor V. Nikitin; Alexander A. Nazarov; Dmitry V. Bobin (Статистика и экономика, 2016)
Algorithm of the creation integral factor for estimation ofthe region’s investment potential is given in the article. It is founded on the main component method, using intwo stages. First at the rate of primary factors. Then at the rate of factors, that characterizing investmentpotential. Comparison given algorithm with method ofthe national rating agency «Expert RA» is presented.